Fish dryer machine technology based on cartridge heater through the utilization of immune stimulant ions - Prasasti Pambayun Anjarwati; Marsono Marsono; Yayi Febdia Pradani (Universitas Sarjanawiyata Tamansiswa, 2025)
The Coordinating Minister for Maritime Affairs believes that Indonesia is experiencing an increase in exports, particularly in the fisheries sector. This is very important because Indonesian waters consist of 44.7% fish, and fisheries are one of Indonesia's key commodity advantages. However, abundant natural resources alone do not guarantee that a nation will become superior if not accompanied by good human resources as well. The issue of fish drying is a crucial problem in the fish processing sector, including for UKM Jaya Utama in Probolinggo City. UKM Jaya Utama still uses traditional drying methods, relying on sunlight as the main drying tool. As a result, UKM Jaya Utama faces drying challenges during the rainy season. The cartridge heater-based fish dryer machine is a machine specially designed for drying and preservation, offering an alternative solution for fish drying during the rainy season and extending the shelf life of the fish. The research method used was an R&D approach with mackerel fish as the research sample, with a capacity of 10 to 15 kg per drying cycle. The machine trial results showed improved work efficiency by reducing the drying duration from 6 hours without the machine to just 2 hours, with potential profit increases of up to 3.6 times.